Evaluation of Turkey Mushroom Export - Emine Emel Ak; Yüksel Tüzel; Erkan Eren; Funda Atilla (Turkish Journal of Agriculture: Food Science and Technology)
Turkey is gene center of many plant species and is a country that different endemic plant species are found. A vast geography and the presence of different climatic conditions cause either diversity of plant genetic resources or macro fungi species. Many species of mushrooms grow spontaneously in nature. According to the demand from different country preferred different mushroom species, some mushroom species collected from nature are exported each year. In this study, it was aimed to determine the properties of macro fungus exporting companies resulting in an evaluation based on exported macro fungus species, the amount, regions where the species are collected and mushroom exportation.